Better estimation of origin-destination matrix using automated intersection movement count data - Tuydes-Yaman, Hediye; Altintasi, Oruc; Şendil, Nuri (Canadian Science Publishing, 2015)
Intersection movements carry more disaggregate information about origin-destination (O-D) flows than link counts in a traffic network. In this paper, a mathematical formulation is presented for O-D matrix estimation using intersection counts, which is based on an existing linear programming model employing link counts. The proposed model estimates static O-D flows for uncongested networks assuming no a priori information on the O-D matrix. Both models were tested in two hypothetical networks previously used in O-D matrix studies to monitor their performances assuming various numbers of count location and measurement errors. Two new measures were proposed to evaluate the model characteristics of O-D flow estimation using traffic counts. While both link count based and intersection count based models performed with the same success under complete data collection assumption, intersection count based formulation estimated the O-D flows more successfully under decreasing number of observation locations. Also, the results of the 30 measurement error scenarios revealed that it performs more robustly than the link count based one; thus, it better estimates the O-D flows.
Keywords: origin-destination matrix estimation; intersection movement count; link count; automated traffic counts; linear programming